Fidelity of Implementation: Understanding Why and When Programs Work. Issue 4 (October 2019) - Lakin, Joni M.; Rambo-Hernandez, Karen
Advancing the science of gifted education requires that researchers and educators better understand when and why (and for whom) programs and services are effective. Assessing Fidelity of Implementation (FoI) is key to achieving this level of understanding and can be incorporated into formative or summative evaluations and formal or informal processes. FoI is especially critical when programs are being scaled up to new contexts. This article explores FoI in terms of defining the program and identifying important moderators of implementation.